Metasploit revealed : secrets of the expert pentester : build your defense against complex attacks : a course in three modules. - Rahalkar, Sagar; Jaswal, Nipun (Packt Publishing, 2017)
Exploit the secrets of Metasploit to master the art of penetration testing. About This Book Discover techniques to integrate Metasploit with the industry's leading tools Carry out penetration testing in highly-secured environments with Metasploit and acquire skills to build your defense against organized and complex attacks Using the Metasploit framework, develop exploits and generate modules for a variety of real-world scenarios Who This Book Is For This course is for penetration testers, ethical hackers, and security professionals who'd like to master the Metasploit framework and explore approaches to carrying out advanced penetration testing to build highly secure networks. Some familiarity with networking and security concepts is expected, although no familiarity of Metasploit is required. What You Will Learn Get to know the absolute basics of the Metasploit framework so you have a strong foundation for advanced attacks Integrate and use various supporting tools to make Metasploit even more powerful and precise Test services such as databases, SCADA, and many more Attack the client side with highly advanced techniques Test mobile and tablet devices with Metasploit Understand how to Customize Metasploit modules and modify existing exploits Write simple yet powerful Metasploit automation scripts Explore steps involved in post-exploitation on Android and mobile platforms In Detail Metasploit is a popular penetration testing framework that has one of the largest exploit databases around. This book will show you exactly how to prepare yourself against the attacks you will face every day by simulating real-world possibilities. This learning path will begin by introducing you to Metasploit and its functionalities. You will learn how to set up and configure Metasploit on various platforms to create a virtual test environment. You will also get your hands on various tools and components and get hands-on experience with carrying out client-side attacks. In the next part of this learning path, you'll develop the ability to perform testing on various services such as SCADA, databases, IoT, mobile, tablets, and many more services. After this training, we jump into real-world sophisticated scenarios where performing penetration tests are a challenge. With real-life case studies, we take you on a journey through client-side attacks using Metasploit and various scripts built on the Metasploit framework. The final instalment of your learning journey will b ...